Copper and copper alloy part surface anti-corrosion process and application thereof
Complex passivation electrochemical film is formed through anhydrous ethanol soaking, ultrasonic cleaning, alkaline solution soaking and electrochemical treatment. Combined with corrosion-resistant sealing agent on the surface of the electrical contact and infrared light oven curing, the copper alloy parts are solved in harsh environments The corrosion problem significantly improves corrosion resistance and service life, and reduces maintenance costs and safety accident risks.
Patent Information
- Application Number
- CN202411263400.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-07
AI Technical Summary
Copper and copper alloy parts are susceptible to corrosion in harsh environments, have short service life, high maintenance costs, and have the risk of safety accidents. The existing technology is difficult to meet the corrosion resistance requirements of high-speed rail and rail transit contact networks.
After soaking with anhydrous ethanol and ultrasonic cleaning, alkaline solution soaking and electrochemical treatment are carried out to form a stable complexed passivation electrochemical film, and cured through an electrical contact surface anti-corrosion sealant and infrared light oven to form a uniform and dense anti-corrosion film layer.
It significantly improves the corrosion resistance and service life of copper and copper alloy parts, reduces maintenance costs, reduces the risk of safety accidents, and maintains stable electrical contact performance within the high temperature range.
Smart Images

Figure CN119265669A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper and copper alloy surface treatment, and in particular to a copper and copper alloy component surface anti-corrosion process and application thereof. Background Art
[0002] With the rapid development of high-speed railways, overhead lines are spread across the country, serving various climates and geographical environments.
[0003] In such a complex atmospheric environment, copper and its alloy parts face severe corrosion challenges. Corrosive media such as CN - NH4 + , Cl - Plasma, strong electric fields and industrial pollutants will have a serious impact on the corrosion resistance and physical and chemical properties of copper and copper alloys. Especially under conditions of humidity, heat, high salt, low temperature, acid rain, etc., the corrosion resistance and stability of copper and copper alloys will drop sharply.
[0004] In the traditional anti-corrosion treatment of copper and copper alloy parts, polishing anti-corrosion technology is usually used to achieve the purpose of anti-corrosion by processing the surface of the workpiece to make it smooth and reduce the adhesion of pollutants. However, when this method reaches a critical humidity value (50% to 70%), pollutants in the atmosphere will dissolve the water film, causing the water film to acidify and the stability of the protective film to decrease. As a result, corrosion products such as Cu2(OH)2CO3 (patina) will be produced on the surface of copper and copper alloys, which not only affects the appearance, but also causes the physical and chemical properties of the material surface to deteriorate, shortening the service life of copper alloy products.
[0005] In addition, when copper and copper alloy parts are used in harsh working conditions, surface corrosion will cause serious stains, aging, and dirt accumulation, affecting the stability and safety of electrical contact, and may even cause accidents such as poor contact, insulation, flashover, pollution flash, corona arc discharge, etc., leading to large-scale and prolonged power outages, causing railway production safety accidents and major economic losses.
[0006] Therefore, developing a scientific and reasonable corrosion and protection design and manufacturing process for copper and copper alloy parts is of great practical significance and urgency for extending the service life of parts, reducing production and maintenance costs, and preventing the occurrence of power supply production safety accidents.
[0007] China's invention patent CN111394718B discloses a passivation solution and a copper surface film treatment method. The passivation solution includes the following components by weight: 0.5-2 parts of fluorotantalate, 1-5 parts of metavanadate, 0.5-2 parts of corrosion inhibitor and 0.5-5 parts of surfactant. The copper surface film treatment method includes the steps of degreasing, polishing, film removal, passivation and drying. The invention is simple to operate, has a fast film forming speed, and a good passivation effect, and can make the copper workpiece after passivation have excellent corrosion resistance. However, the passivation solution and copper surface film treatment method of the invention cannot meet the corrosion resistance requirements of copper and copper alloy parts used in high-speed rail and rail transit contact networks. Summary of the invention
[0008] In view of the problems of the prior art that copper and copper alloy components are susceptible to corrosion, have a short service life and high maintenance costs under harsh working conditions, the present invention provides a new complex passivation anti-corrosion process, which significantly improves the corrosion resistance of components by forming a stable anti-corrosion conversion film, extends the service life, and reduces maintenance costs. It is suitable for use in high-speed railways and rail transit contact networks, and reduces the risk of safety accidents.
[0009] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0010] A surface anti-corrosion process for copper and copper alloy parts is as follows:
[0011] Step 1: Soak copper and copper alloy parts and components in anhydrous ethanol to remove industrial oil stains on the surface. Use ultrasonic equipment to assist cleaning during soaking. After cleaning, use pure water to clean the surface to remove residual anhydrous ethanol and emulsified oil stains. Soak the cleaned copper and copper alloy parts and components in an alkaline solution at 60-80°C for 1-5 minutes, and then rinse the copper and copper alloy parts and components with pure water to ensure that the surface is clean and free of residue.
[0012] Step 2, prepare an environmentally friendly complex passivation electrolyte solution for electrochemical treatment; use copper and copper alloy parts materials as working electrodes, platinum electrodes as counter cathodes, and Ag / AgCl electrodes as reference electrodes to perform current and potential incremental scanning; then use a square wave alternating electric field to perform complex passivation electrochemical passivation treatment on the surface of copper and copper alloy parts materials, and the film thickness after the complex passivation electrochemical passivation treatment is completed is not less than 0.4 μm;
[0013] Step 3: After the electrochemical conversion film treatment is completed, the surface of the metal material is cleaned with pure water, and then dried with hot air at 50-70° C. to obtain a protective base metal material with surface activity;
[0014] Step 4, preheating the surface-active protective base metal material to 40-50° C., heating the electrical contact surface anti-corrosion sealant to 40-50° C., and then dipping the sealant for 20-40 seconds, placing the coated workpiece in an infrared light oven, photopolymerizing and solidifying the film at 100-140° C. for 40-60 minutes, drying, and keeping warm for 0.5-2 hours to obtain dried copper and copper alloy parts;
[0015] Step 5, taking out the dried copper and copper alloy parts from the oven and placing them at room temperature for natural cooling;
[0016] Step 6: Wrap the qualified workpiece with anti-scratch material and put it into a protective box to obtain the finished product.
[0017] The ultrasonic wave used for the ultrasonic cleaning in step 1 has a frequency of 20 to 60 kHz, a power of 200 to 400 W, and a duration of 20 to 30 min.
[0018] In step 2, the alkaline solution is composed of sodium carbonate and sodium hydroxide, wherein the sodium carbonate content in the alkaline solution is 10-18 g / L and the sodium hydroxide content is 15-22 g / L.
[0019] In the step 2, the low potential Ea of the incremental scan is 80-120 mV, the high potential Eb is 350-450 mV, the scan speed is 20-60 mV / min, and it is repeated 1-5 times.
[0020] In the step 2, the square wave alternating electric field has the following parameters: high potential Eh 500mV to 700mV, low potential El -150mV to 0mV, carrier time t 10 to 30 minutes, alternating electric field period T 0.01 to 0.1 seconds, frequency f 10 to 30Hz, and duty cycle k 10% to 80%.
[0021] The concentrations of the various substances in the formula of the environmentally friendly complex passivating electrolyte solution are as follows: 8-12 g / L sodium dihydrogen phosphate, 3-5 g / L tartaric acid, 7-9 g / L sodium persulfate, 1-3 g / L potassium permanganate, 7-9 g / L terminal epoxy polyether silicone oil, 0.5-2 g / L sodium fluorotitanate, 1-3 g / L ammonium vanadate, 0.5-2 g / L polyvinyl pyrrolidone, 5-7 g / L sodium gluconate, 25-60 g / L sodium nitrate, 8-24 g / L sodium bicarbonate, and the rest is pure water.
[0022] A surface anti-corrosion copper and copper alloy component is manufactured by adopting the surface anti-corrosion process of the copper and copper alloy component.
[0023] The application of the surface corrosion-resistant copper and copper alloy parts in high-speed railways and rail transit contact networks.
[0024] In the surface corrosion protection process of copper and copper alloy parts of the present invention, the functions of various substances are as follows:
[0025] Anhydrous ethanol is a degreasing cleaning agent used to remove oil stains on the copper surface. Ultrasonic equipment assisted cleaning to enhance the cleaning effect.
[0026] An alkaline solution consisting of sodium carbonate and sodium hydroxide is used to further clean the copper, removing any remaining grease and impurities in preparation for the electrochemical treatment.
[0027] The environmentally friendly complex passivation electrolyte solution contains sodium nitrate and sodium bicarbonate, which provides a conductive environment for electrochemical photochemical film formation and promotes the formation of the film layer during the electrochemical treatment process.
[0028] The environmentally friendly complex passivation electrolyte solution contains sodium dihydrogen phosphate, tartaric acid, sodium persulfate, potassium permanganate and other ingredients, which are used to form a stable complex passivation anti-corrosion film layer on the copper surface.
[0029] Sodium dihydrogen phosphate is used as a buffer to maintain the pH value of the environmentally friendly complex passivating electrolyte solution. At the same time, it may participate in the formation of a phosphate film during the film-forming process to increase the corrosion resistance of the film layer.
[0030] Tartaric acid, as a chelating agent, can form a stable complex with metal ions, which helps to form a uniform protective film on the metal surface.
[0031] Sodium persulfate, as an oxidant, helps to form an oxide film on the metal surface, improving the density and adhesion of the film.
[0032] Potassium Permanganate is a strong oxidizing agent that may be used to improve the corrosion and wear resistance of the passive film.
[0033] End-epoxy polyether silicone oil may be used to adjust the adhesion and uniformity of the film layer in an environmentally friendly complex passivating electrolyte solution, thereby improving the protective performance of the film layer.
[0034] Sodium fluorotitanate and ammonium vanadate, as components of an environmentally friendly complex passivating electrolyte solution, may be used to increase the corrosion resistance and stability of the film layer.
[0035] Polyvinyl pyrrolidone may be used to improve the rheological properties of environmentally friendly complex passivating electrolyte solutions and promote the uniform formation of film layers.
[0036] Sodium gluconate may be used to adjust the viscosity of environmentally friendly complex passivating electrolyte solutions and the film-forming properties of the film layer.
[0037] pH regulators are used to precisely control the pH value of environmentally friendly complex passivating electrolyte solutions to ensure that the film-forming reaction proceeds under optimal conditions.
[0038] Sealing agents are used for anti-corrosion solid film protection of electrical contact surfaces, enhancing the corrosion resistance of the film layer and providing an additional protective layer.
[0039] Through the combined effects of these substances and steps, the present invention achieves efficient treatment of surface corrosion protection of copper and copper alloy parts, and improves the corrosion resistance and service life of the parts.
[0040] The technical solution of the present invention is an innovative complex passivation anti-corrosion process technology for copper and copper alloy contact network parts. The solution achieves the formation of a chemically bonded polymer passivation complex conversion film on the surface of copper and copper alloy parts through a series of fine surface treatment steps, including degreasing and cleaning, complex passivation electrochemical passivation treatment film formation, and electrical contact surface anti-corrosion solid film protection. This film layer can effectively isolate the corrosive medium and prevent it from contacting the metal matrix, thereby significantly improving the corrosion resistance of the parts.
[0041] The technical effect of the present invention is that it significantly improves the corrosion resistance and stability of copper and copper alloy parts. The formation of the conversion film not only enhances the durability of the parts in harsh environments, but also ensures a long-term and reliable anti-corrosion effect due to its self-healing repair ability. In addition, the film layer treated by this technology does not increase the contact resistance, maintains the electrical contact performance of the metal surface, and at the same time improves the operability and maintainability of the parts, prolongs their service life, and reduces maintenance costs.
[0042] Compared with the prior art, it has the following beneficial effects:
[0043] 1) The complex passivation anti-corrosion process technology adopted in the present invention can effectively isolate the corrosive medium by forming a conversion film on the surface of copper and copper alloy parts, providing better corrosion resistance than traditional anti-corrosion technology, and is particularly suitable for use in high-speed railways and rail transit contact networks.
[0044] 2) The film layer prepared by the present invention is not only uniform and dense, forming a stable chemical bond with the metal surface, but also has self-healing ability, which means that the film layer can self-repair when it is slightly damaged, thereby maintaining its anti-corrosion function for a long time.
[0045] 3) The anti-corrosion solid film protection process of the electrical contact surface of the present invention ensures that the contact resistance of the treated parts does not increase, the resistivity remains stable, and at the same time, it can work stably for a long time in a wide temperature range (-80 to +120°C), thereby improving the safety and reliability of the electrical contact.
[0046] 4) The metal surface after solid film of the present invention has hydrophobicity, low temperature resistance and self-cleaning properties, which reduces dust adsorption and reduces the surface friction coefficient, thereby improving the operability of parts and components, and significantly increasing the service life of parts and components, reducing maintenance costs and replacement cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1This is a diagram of a copper component after being processed using the copper component surface anti-corrosion process according to Example 1 of the present invention. DETAILED DESCRIPTION
[0048] Main sources of substances:
[0049] Epoxy-terminated polyether active silicone oil: Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., product number: P20230618.
[0050] Methoxypolyethylene glycol silane: Beijing Beike New Materials Technology Co., Ltd., item number: bknm2012010-1.
[0051] Sealing agent: Shaoguan Meituoweizhi Chemical Co., Ltd., model: A20-189.
[0052] The remaining raw materials in the examples and comparative examples of the present invention are all conventional commercially available products.
[0053] The design idea of the present invention is to develop a surface anti-corrosion process for copper and copper alloy parts to cope with the corrosion problems caused to copper and copper alloy parts in harsh environments such as high humidity and heavily polluted areas used in high-speed rail and rail transit contact networks. The process aims to form a uniform, dense and firmly bonded anti-corrosion film layer with the metal matrix through a series of refined surface treatment steps, including degreasing and cleaning, complex passivation electrochemical passivation treatment film formation, and electrical contact surface anti-corrosion solid film protection. This film can effectively isolate the contact between the corrosive medium and the metal matrix, improve the corrosion resistance of the parts, extend the service life, reduce maintenance costs, and reduce the risk of safety accidents caused by corrosion. In addition, the formula of the environmentally friendly complex passivation electrolyte solution of the present invention is specially designed, using sodium dihydrogen phosphate, sodium persulfate, end-epoxy polyether silicone oil and other ingredients, and accurately controlling the pH value to achieve the best anti-corrosion effect. Through this comprehensive technical solution, the present invention not only improves the corrosion resistance of copper and copper alloy parts, but also ensures its reliability and stability in high-speed rail and rail transit contact networks.
[0054] Example 1
[0055] A copper parts surface anti-corrosion process is as follows:
[0056] Step 1. Soak the copper parts in anhydrous ethanol to remove the oil on the surface. Use ultrasonic equipment to assist cleaning during soaking. The frequency of the ultrasonic wave is 40kHz, the power is 300W, and the time is 30 minutes. After cleaning, rinse with water to remove the residual anhydrous ethanol and emulsified oil. Soak the cleaned copper parts in an alkaline solution at 70°C for 4 minutes. The alkaline solution is composed of sodium carbonate and sodium hydroxide. The sodium carbonate in the alkaline solution is 15g / L and the sodium hydroxide is 20g / L. Then use pure water to rinse the copper parts to ensure that the surface is clean and free of residue.
[0057] Step 2, prepare an environmentally friendly complex passivation electrolyte solution for electrochemical treatment, use the copper parts as the working electrode, the platinum electrode as the counter electrode, and the Ag / AgCl electrode as the reference electrode, perform current and potential incremental scanning, the low potential Ea of the incremental scanning is 100mV, the high potential Eb is 400mV, the scanning speed is 40mV / min, and repeat 3 times; then use a square wave alternating electric field to perform complex passivation electrochemical passivation treatment on the surface of the copper parts, and the parameters are set as: high potential Eh 600mV, low potential El0mV, carrier time t 20 minutes, alternating electric field period T0.05 seconds, frequency f20Hz, duty cycle k 30%; after the complex passivation anti-corrosion process is completed, the film thickness is 0.5μm;
[0058] Step 3: After the electrochemical conversion film treatment is completed, the copper parts are rinsed with pure water and then dried with 60°C hot air to obtain a protective base metal material with surface activity;
[0059] Step 4, preheating the surface-active protective base metal material to 48°C, heating the electrical contact surface anti-corrosion sealant to 48°C and then dipping the sealant for 30 seconds, placing the coated workpiece in an infrared light oven at 120°C for photopolymerization solid film for 60 minutes, drying at 120°C for 30 minutes, and keeping warm for 1 hour to obtain a dried copper part;
[0060] Step 5: Take the dried copper parts out of the oven and place them at room temperature for natural cooling;
[0061] Step 6: Wrap the qualified workpiece with anti-scratch material and put it into a protective box to obtain the finished product.
[0062] The concentrations of the various substances in the formula of the environmentally friendly complex passivating electrolyte solution are as follows: 10 g / L sodium dihydrogen phosphate, 4 g / L tartaric acid, 8 g / L sodium persulfate, 2 g / L potassium permanganate, 8 g / L terminal epoxy polyether silicone oil, 1 g / L sodium fluorotitanate, 2 g / L ammonium vanadate, 1 g / L polyvinyl pyrrolidone, 6 g / L sodium gluconate, 40 g / L sodium nitrate, 15 g / L sodium bicarbonate, and the rest is water.
[0063] Example 2
[0064] A copper component surface anti-corrosion process is basically the same as that in Example 1, the only difference being that the formula of the environmentally friendly complex passivating electrolyte solution is different.
[0065] The concentrations of the substances in the formula of the environmentally friendly complex passivating electrolyte solution are as follows: 10 g / L phytic acid, 4 g / L tartaric acid, 8 g / L sodium persulfate, 2 g / L potassium permanganate, 8 g / L terminal epoxy polyether silicone oil, 1 g / L sodium fluorotitanate, 2 g / L ammonium vanadate, 1 g / L polyvinyl pyrrolidone, 6 g / L sodium gluconate, 40 g / L sodium nitrate, 15 g / L sodium bicarbonate, and the rest is water.
[0066] Example 3
[0067] A copper component surface anti-corrosion process is basically the same as that in Example 1, the only difference being that the formula of the environmentally friendly complex passivating electrolyte solution is different.
[0068] The concentrations of the various substances in the formula of the environmentally friendly complex passivating electrolyte solution are as follows: 10 g / L sodium dihydrogen phosphate, 4 g / L tartaric acid, 8 g / L ammonium cerium nitrate, 2 g / L potassium permanganate, 8 g / L terminal epoxy polyether silicone oil, 1 g / L sodium fluorotitanate, 2 g / L ammonium vanadate, 1 g / L polyvinyl pyrrolidone, 6 g / L sodium gluconate, 40 g / L sodium nitrate, 15 g / L sodium bicarbonate, and the rest is water.
[0069] Example 4
[0070] A copper component surface anti-corrosion process is basically the same as that in Example 1, the only difference being that the formula of the environmentally friendly complex passivating electrolyte solution is different.
[0071] The concentrations of the substances in the formula of the environmentally friendly complex passivating electrolyte solution are as follows: 10 g / L sodium dihydrogen phosphate, 4 g / L tartaric acid, 8 g / L sodium persulfate, 2 g / L potassium permanganate, 8 g / L methoxypolyethylene glycol silane, 1 g / L sodium fluorotitanate, 2 g / L ammonium vanadate, 1 g / L polyvinyl pyrrolidone, 6 g / L sodium gluconate, 40 g / L sodium nitrate, 15 g / L sodium bicarbonate, and the rest is water.
[0072] Comparative Example 1
[0073] A copper component surface anti-corrosion process is basically the same as that in Example 1, the only difference being that the formula of the environmentally friendly complex passivating electrolyte solution is different.
[0074] The concentrations of the various substances in the formula of the environmentally friendly complex passivating electrolyte solution are as follows: 10 g / L sodium dihydrogen phosphate, 4 g / L tartaric acid, 8 g / L sodium persulfate, 2 g / L potassium permanganate, 8 g / L terminal epoxy polyether silicone oil, 2 g / L ammonium vanadate, 1 g / L polyvinyl pyrrolidone, 6 g / L sodium gluconate, 40 g / L sodium nitrate, 15 g / L sodium bicarbonate, and the rest is water.
[0075] Comparative Example 2
[0076] A copper component surface anti-corrosion process is basically the same as that in Example 1, the only difference being that the formula of the environmentally friendly complex passivating electrolyte solution is different.
[0077] The concentrations of the various substances in the formula of the environmentally friendly complex passivating electrolyte solution are as follows: 10 g / L sodium dihydrogen phosphate, 4 g / L tartaric acid, 8 g / L sodium persulfate, 2 g / L potassium permanganate, 8 g / L terminal epoxy polyether silicone oil, 1 g / L sodium fluorotitanate, 1 g / L polyvinyl pyrrolidone, 6 g / L sodium gluconate, 40 g / L sodium nitrate, 15 g / L sodium bicarbonate, and the rest is water.
[0078] Comparative Example 3
[0079] A copper component surface anti-corrosion process is basically the same as that in Example 1, the only difference being that the formula of the environmentally friendly complex passivating electrolyte solution is different.
[0080] The environmentally friendly complex passivation electrolyte solution is a commercially available product from Dongguan Xinshengxun Passivation Materials Co., Ltd., item number: BAM-2003.
[0081] Test Example 1
[0082] Corrosion test
[0083] A 5% NaCl solution with a pH of 6.8 was used, the temperature in the box was 35±2°C, and the humidity was above 85%. The test was conducted for 800 hours. After the test, the surface solution was rinsed off with clean water and the passivation layer was observed to see if there were peeling, shedding, or discoloration. The test results are shown in Table 1.
[0084] Table 1
[0085]
[0086] Test Example 2
[0087] High temperature wear resistance test
[0088] A high temperature wear tester was used with a friction temperature of 300°C, a load of 40N, a friction time of 30min, and a rotation speed of 100r / min. The wear resistance was comprehensively judged by the friction coefficient and the amount of wear. The test results are shown in Table 2.
[0089] Table 2
[0090] Experimental protocol Average friction coefficient Wear amount (mg) Example 1 0.0864 3.6 Example 2 0.1035 5.8 Example 3 0.1142 6.2 Example 4 0.1085 5.9 Comparative Example 1 0.1351 7.1 Comparative Example 2 0.1275 6.8 Comparative Example 3 0.1648 9.2
[0091] It can be seen from test examples 1 to 2 that the copper parts obtained in Example 1 of the present invention have good corrosion resistance and high temperature wear resistance.
[0092] In Example 1, sodium dihydrogen phosphate is used as a component of the environmentally friendly complex passivation electrolyte solution, which shows better corrosion resistance and high temperature wear resistance than phytic acid in Example 2. Sodium dihydrogen phosphate can form a stable phosphate film in an aqueous solution, and this film layer provides stronger corrosion protection on the surface of the copper alloy because it can more effectively isolate the metal from the contact with the corrosive medium. At the same time, the phosphate film layer may be converted into a compound with high hardness and thermal stability, thereby improving the wear resistance. In addition, the chemical stability of sodium dihydrogen phosphate and its ability to bind to the metal surface may also be more superior, which helps to form a uniform and highly adhesive film layer. In contrast, although phytic acid has a certain chelating ability, it may not be as good as sodium dihydrogen phosphate in terms of uniformity, stability of film formation and wear resistance at high temperatures, so it is not as good as Example 1 in terms of corrosion resistance and wear resistance. By using 20wt% hydrochloric acid as a pH regulator to ensure that the environmentally friendly complex passivation electrolyte solution is maintained at pH 3, the film formation process is further optimized, so that the passivation film of Example 1 is more outstanding in chemical and physical properties.
[0093] The sodium persulfate used in Example 1, as a strong oxidant, can effectively participate in the reaction in the environmentally friendly complex passivation electrolyte solution, and promote the formation of a uniform and dense oxide film on the copper surface. This oxide film can not only provide excellent corrosion resistance, but also remain stable at high temperatures, thereby reducing wear. The sulfate ions produced by sodium persulfate may form a stable chelate with the copper surface, further enhancing the adhesion and protective effect of the film layer. In contrast, although the ammonium cerium nitrate used in Example 3 can also provide oxidation, the cerium ions may not be as good as the sulfate ions in forming stable chemical bonds on the copper surface. In addition, ammonium cerium nitrate may be thermally unstable at high temperatures, resulting in wear resistance that is not as good as sodium persulfate. Therefore, the role of sodium persulfate in the environmentally friendly complex passivation electrolyte solution may be more conducive to the formation of a surface protective layer with good corrosion resistance and high-temperature wear resistance, which may be the reason why Example 1 exhibits better performance than Example 3.
[0094] The end-epoxy polyether silicone oil used in Example 1 can form a more stable chemical bond on the copper surface due to the presence of its end epoxy group, which enhances the adhesion between the passivation film and the metal substrate, thereby providing better anti-corrosion performance. The long-chain polyether structure of the end-epoxy polyether silicone oil may also help to form a more uniform and continuous protective film, which can resist the penetration of corrosive media to a certain extent. In addition, in the high-temperature wear resistance test, the film layer formed by the end-epoxy polyether silicone oil may have better thermal stability and mechanical strength, which helps to reduce wear during high-temperature friction. In contrast, although the methoxy polyethylene glycol silane used in Example 4 also provides a certain protective effect, its methoxy group may not be able to form a strong chemical bond with the metal surface like the end epoxy group, so it may be slightly inferior in terms of anti-corrosion performance and high-temperature wear resistance. The protective film of methoxy polyethylene glycol silane may be more easily damaged or detached at high temperature or long-term use, resulting in a decrease in anti-corrosion and wear resistance.
[0095] The formula of the environmentally friendly complex passivating electrolyte solution in Example 1 contains sodium fluorotitanate and ammonium vanadate, which play a key role in the excellent corrosion resistance and high-temperature wear resistance exhibited by this example. Sodium fluorotitanate, as a fluoride source, can form a stable titanium fluoride film layer on the surface of the copper alloy during the passivation process. This film layer can not only effectively improve the corrosion resistance of the metal surface, but also maintain its structural stability at high temperatures, thereby reducing the wear rate. Ammonium vanadate, as a vanadium source, introduces vanadium elements into the passivation film, which may form complex oxides or hydroxides with the copper surface, enhance the adhesion and hardness of the film layer, and further improve the wear resistance. In addition, the addition of vanadium may also help to improve the scratch resistance and impact resistance of the passivation film. In contrast, sodium fluorotitanate and ammonium vanadate are lacking in Comparative Examples 1 and 2, which may result in insufficient corrosion resistance and wear resistance of the passivation film. Without sodium fluorotitanate, the passivation film may not have a sufficient fluoride layer, thereby reducing the resistance to corrosive media; and without ammonium vanadate, the passivation film may be insufficient in hardness and adhesion, resulting in reduced wear resistance. Therefore, the synergistic effect of sodium fluorotitanate and ammonium vanadate is an important factor in achieving better performance in Example 1.
[0096] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A surface corrosion protection process for copper and copper alloy parts, characterized in that: The process is as follows: Step 1: Soak copper and copper alloy parts and components in anhydrous ethanol to remove industrial oil stains on the surface. Use ultrasonic equipment to assist cleaning during soaking. After cleaning, use pure water to clean the surface to remove residual anhydrous ethanol and emulsified oil stains. Soak the cleaned copper and copper alloy parts and components in an alkaline solution at 60-80°C for 1-5 minutes, and then rinse the copper and copper alloy parts and components with pure water to ensure that the surface is clean and free of residue. Step 2, prepare an environmentally friendly complex passivation electrolyte solution for electrochemical treatment; use copper and copper alloy parts materials as working electrodes, platinum electrodes as counter cathodes, and Ag / AgCl electrodes as reference electrodes to perform current and potential incremental scanning; then use a square wave alternating electric field to perform complex passivation electrochemical passivation treatment on the surface of copper and copper alloy parts materials, and the film thickness after the complex passivation electrochemical passivation treatment is completed is not less than 0.4 μm; Step 3: After the electrochemical conversion film treatment is completed, the surface of the metal material is cleaned with pure water, and then dried with hot air at 50-70° C. to obtain a protective base metal material with surface activity; Step 4, preheating the surface-active protective base metal material to 40-50° C., heating the electrical contact surface anti-corrosion sealant to 40-50° C., and then dipping the sealant for 20-40 seconds, placing the coated workpiece in an infrared light oven, photopolymerizing and solidifying the film at 100-140° C. for 40-60 minutes, drying, and keeping warm for 0.5-2 hours to obtain dried copper and copper alloy parts; Step 5, taking out the dried copper and copper alloy parts from the oven and placing them at room temperature for natural cooling; Step 6: Wrap the qualified workpiece with anti-scratch material and put it into a protective box to obtain the finished product.
2. The surface anti-corrosion process for copper and copper alloy parts according to claim 1, characterized in that: The ultrasonic wave used for the ultrasonic cleaning in step 1 has a frequency of 20 to 60 kHz, a power of 200 to 400 W, and a duration of 20 to 30 min.
3. The surface anti-corrosion process for copper and copper alloy parts according to claim 1, characterized in that: The alkaline solution in step 2 is composed of sodium carbonate and sodium hydroxide, wherein the sodium carbonate content in the alkaline solution is 10-18 g / L and the sodium hydroxide content is 15-22 g / L.
4. The surface anti-corrosion process for copper and copper alloy parts according to claim 1, characterized in that: In the step 2, the low potential Ea of the incremental scan is 80-120 mV, the high potential Eb is 350-450 mV, the scan speed is 20-60 mV / min, and it is repeated 1-5 times.
5. The surface anti-corrosion process for copper and copper alloy parts according to claim 1, characterized in that: In the step 2, the square wave alternating electric field has the following parameters: high potential Eh 500mV to 700mV, low potential El -150mV to 0mV, carrier time t 10 to 30 minutes, alternating electric field period T 0.01 to 0.1 seconds, frequency f 10 to 30Hz, and duty cycle k 10% to 80%.
6. The surface anti-corrosion process for copper and copper alloy parts according to claim 1, characterized in that: The concentrations of the various substances in the formula of the environmentally friendly complex passivating electrolyte solution are as follows: 8-12 g / L sodium dihydrogen phosphate, 3-5 g / L tartaric acid, 7-9 g / L sodium persulfate, 1-3 g / L potassium permanganate, 7-9 g / L terminal epoxy polyether silicone oil, 0.5-2 g / L sodium fluorotitanate, 1-3 g / L ammonium vanadate, 0.5-2 g / L polyvinyl pyrrolidone, 5-7 g / L sodium gluconate, 25-60 g / L sodium nitrate, 8-24 g / L sodium bicarbonate, and the rest is pure water.
7. A surface corrosion-resistant copper and copper alloy component, characterized in that: The method is manufactured by the process as described in any one of claims 1 to 6.
8. An application of surface corrosion-resistant copper and copper alloy parts, characterized in that: Application of the surface corrosion-resistant copper and copper alloy parts as described in claim 7 in high-speed railways and rail transit contact networks.
Citation Information
Patent Citations
Passivation solution and copper surface film formation treatment method
CN111394718B